Stile e scrittura della matematica secondo Gilles-Gaston Granger (Nóema, 2025)
Style and writing in mathematics according to Gilles-Gaston GrangerThis article aims to study the philosophical problem of mathematical writing starting from the notion of style developed by Gilles-Gaston Granger in Essai d’une philosophie du style (1968; 1988). After framing the context in which Granger elaborates this notion of style, and after showing some of its theoretical facets, we will proceed with the study of three specific styles of mathematics, namely the Euclidean style, the Cartesian style, and the vector style. Following Granger, the theoretical criterion for best noting the variations of these three styles will be the concept of geometric magnitude. In light of the analysis of the three mathematical styles, we will draw some observations and critical notes on Granger’s stylistic method.
Keywords: Style; Philosophy of Mathematics; Philosophie Mathématique; Gilles-Gaston Granger; Algebraic Geometry